Discretionary Disclosure of Proprietary Information in a Multisegment Firm - Arya, Anil; Frimor, Hans; Mittendorf, Brian (Management Science, 2010)
The seminal “unraveling” result in the disclosure literature posits that discretion inevitably leads to full disclosure, even when such disclosure has detrimental consequences. In this paper, we revisit optimal disclosure of proprietary information when firms compete in multiple markets. The analysis demonstrates that in the presence of multiple segments, the unraveling result applies at the firmwide level but not necessarily segment by segment. Instead, when the firm has an ex ante desire to withhold information and segments are sufficiently similar, the ex post disclosure equilibrium entails aggregation of segment details. Aggregation arises because any ex post temptation to disaggregate and reveal particularly favorable news in one segment entails revealing unfavorable news in another segment. A desire to balance profits across segments then leads a firm to disclose firmwide information (a temptation that cannot be avoided), but only in the aggregate.